If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 13 + -3x Solving 25 = 13 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 25 + 3x = 13 + -3x + 3x Combine like terms: -3x + 3x = 0 25 + 3x = 13 + 0 25 + 3x = 13 Add '-25' to each side of the equation. 25 + -25 + 3x = 13 + -25 Combine like terms: 25 + -25 = 0 0 + 3x = 13 + -25 3x = 13 + -25 Combine like terms: 13 + -25 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 6x-4x+10x=49+5x | | 14-12V=4(1-5V)+8V | | -(k-10.9)=1.4k-1.1 | | 3x(-x-3)-2=x(3x-4)+13 | | 65=5(y-86) | | 7x-9=19+x | | -7(3+6V)=-189 | | -6/7-1/7= | | (6x)x2/3 | | 4x+2+5x+3=3x+53 | | 5x+6y+9x= | | -330=10(-5x-3) | | 4x+8x+6x-24=x | | 5-(3-x)=6.5 | | M=682287/967540 | | -10(X-6)=6(10+2X) | | -4x+4(3x-13)=-140 | | 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 | | x^4-2x^3+14x^2-18x+45=0 | | 8k-k-5k+7-2k= | | -15+x+1=31 | | -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) |